2015
DOI: 10.3329/bpj.v17i1.22321
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of DNA with H2TMPyP4+and Ru(II)TMPyP4+: Probable Lead Compounds for African Sleeping Sickness

Abstract: Interactions of DNA with free base porphyrin, tetrakis(1-methylpyridium-4-yl)porphyrin (H 2 TMPyP 4+ ) and its metallo-derivative of ruthenium(II) have been investigated by UV-Vis, fluorescence and circular dichroism (CD) spectroscopy at 0.1 M NaCl, 7.5 pH and 25 °C. The results suggest that Ru(II)TMPyP 4+ interacts with DNA via outside binding in self-stacking manner as indicated by UV-Vis data, a small red shift (∆λ = 3 nm) and a minimal hypochromicity (10%) upon addition of DNA. CD spectra showed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(46 citation statements)
references
References 31 publications
(35 reference statements)
1
44
1
Order By: Relevance
“…The addition of nitrate ion reduces the positive charge of the cationic porphyrin at the transition state through formation of anion-cation-porphyrin adducts that causes the decreasing the reaction rates for negatively charged nickel species [18,58,65]. In our previous study, we also found weak intensities from the Ru 2+ -, Pd 2+ -, Pt 2+ -and [Au(III)TMPyP] 5+ porphyrins in aqueous solution because of the heavy atom effect [40,41]. The fluorescence intensity for the [Ni(II)TMPyP] 4+ complex is significantly decreased upon addition of a low concentration of DNA, and then increased with further addition of DNA (supplementary Figure S-2a).…”
Section: Observed Rate Constants (Kobs) With Ionic Strengthmentioning
confidence: 99%
See 4 more Smart Citations
“…The addition of nitrate ion reduces the positive charge of the cationic porphyrin at the transition state through formation of anion-cation-porphyrin adducts that causes the decreasing the reaction rates for negatively charged nickel species [18,58,65]. In our previous study, we also found weak intensities from the Ru 2+ -, Pd 2+ -, Pt 2+ -and [Au(III)TMPyP] 5+ porphyrins in aqueous solution because of the heavy atom effect [40,41]. The fluorescence intensity for the [Ni(II)TMPyP] 4+ complex is significantly decreased upon addition of a low concentration of DNA, and then increased with further addition of DNA (supplementary Figure S-2a).…”
Section: Observed Rate Constants (Kobs) With Ionic Strengthmentioning
confidence: 99%
“…The intensity of the hump increases with addition of DNA and the fluorescence spectrum is finally centered at 630 nm (supplementary Figure S-2b). These results suggested that the cationic free base porphyrin initially interacts with DNA via negatively charged phosphate network in the presence of a low concentration of DNA, and then de-stacking occurs upon further addition of DNA [40,41]. From the UV-vis and fluorescence spectral results, it is confirmed that both the metalloporphyrin, [Ni(II)TMPyP] 4+ , and the free base porphyrin interact with DNA but their modes of interaction are different.…”
Section: Observed Rate Constants (Kobs) With Ionic Strengthmentioning
confidence: 99%
See 3 more Smart Citations